2020
DOI: 10.1371/journal.pntd.0008242
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Echinococcus multilocularis and Echinococcus granulosus sensu lato in Kyrgyzstan: The A2 haplotype of E. multilocularis is the predominant variant infecting humans

Abstract: Alveolar and cystic echinococcosis (AE, CE) caused by E. multilocularis and E. granulosus s.l., respectively, are considered emerging zoonotic diseases in Kyrgyzstan with some of the world highest regional incidences. Little is known regarding the molecular variability of both species in Kyrgyzstan. In this study we provide molecular data from a total of 72 parasite isolates derived from humans (52 AE and 20 CE patients) and 43 samples from dogs (23 infected with E. multilocularis and 20 with E. granulosus s.l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Although AE intermediate hosts have specific habitat requirements and thus landscape composition is considered as a proxy for their distribution [ 14 ], the lack of adequate data on AE intermediate hosts distribution and abundance also limits our study. Additionally, it remains unknown whether the emergence of AE in Kyrgyzstan might also be due to a higher virulence of the most common variant infecting humans in this country [ 40 ]. More data and genotyping of both human and definitive host populations might help understanding this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although AE intermediate hosts have specific habitat requirements and thus landscape composition is considered as a proxy for their distribution [ 14 ], the lack of adequate data on AE intermediate hosts distribution and abundance also limits our study. Additionally, it remains unknown whether the emergence of AE in Kyrgyzstan might also be due to a higher virulence of the most common variant infecting humans in this country [ 40 ]. More data and genotyping of both human and definitive host populations might help understanding this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Kyrgyz serum samples of treatment-naïve patients included 40 AE and 23 CE patients that were diagnosed and had surgery at City Clinical Hospital #1 in Bishkek, Kyrgyzstan. Case inclusion criteria in both countries were solely based on positive PCR results [ 44 , 45 ] or immunohistochemical-stainings with monoclonal antibodies of resection specimens or biopsies [ 46 ]. Lesions were classified according to WHO standards [ 6 ] and clinical data was noted.…”
Section: Methodsmentioning
confidence: 99%
“…This European E. multilocularis isolate was initially described by Nakao et al (2009) [ 47 ] and was later found in France and Belgium. Molecular analysis was performed as described by Alvarez–Rojas et al (2020) [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…in Kyrgyzstan between 2017 and 2018 [including a genetic characterisation of E . multilocularis [ 67 ] and identification by egg isolation + multiplex-PCR [ 15 ]]. In the study mentioned above, taeniid eggs were concentrated from dog faecal samples as previously described and DNA was isolated combining alkaline lysis and the QIAamp Kit [ 10 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In total, we used 32 faecal samples from dogs collected as part of a large prevalence study for Echinococcus spp. in Kyrgyzstan between 2017 and 2018 [including a genetic characterisation of E. multilocularis [67] and identification by egg isolation + multiplex-PCR [15]]. In the study mentioned above, taeniid eggs were concentrated from dog faecal samples as previously described and DNA was isolated combining alkaline lysis and the QIAamp Kit [10,50] Two aliquots of 400-500 mg were taken from faecal samples of 30 foxes infected with E. multilocularis and five from negative foxes from the same group of animals used for protocols 1A and 1B (diagnosed at necropsy/SCT).…”
Section: Dog Faecal Samplesmentioning
confidence: 99%